Remodeling Pregnancy Exercises with Pelvic Rocking Exercise as Management of Back Pain in Pregnant Women - Darah Ifalahma; Ana Yuliana; Zainie Aboo Bakkar; Rizki Nugraha Wargani; Rara Ayu Puspitasari (Indonesian Journal of Global Health Research, 2025)
The discomfort that often arises during the third trimester of pregnancy and is often complained of by pregnant women is back pain. Back pain in pregnant women can be treated with pregnancy exercises. In pregnancy exercises, the 5th movement, namely rocking back arches, can be continued with the Pelvic Rocking Exercise for optimal results. Objective: The aim of this study was to determine the effectiveness of remodeling pregnancy exercises using pelvic rocking exercise on back pain in pregnant women. Method: Quasi Experimental research method with pretest-posttest with control group design. The purposive sampling sample was 20 third trimester pregnant women with back pain, divided into 2 groups, namely the control group (pregnancy exercise only) and the intervention group (remodeling pregnancy exercise with pelvic rocking exercise). The instrument used was the Numerical Rating Scale pain scale observation sheet. Data analysis with a difference test between pre and post. Results: The results of the back pain scale for pregnant women in the control group after being given pregnancy exercises obtained an average of 11.71, while in the intervention group after being given remodeling pregnancy exercises with pelvic rocking exercise the average was 9.46. The results of data analysis using the Mann-Whitney U-Test showed a p value of 0.001 ≤ 0.05, which means the pain scale in the intervention group decreased more than the pain scale in the control group. Conclusion: Remodeling pregnancy exercise with pelvic rocking exercise is more effective in managing back pain in pregnant women.